25‐hydroxyvitamin D levels in African American and Nigerian women. Issue 4 (4th April 2013) - Durazo‐Arvizu, Ramon A.; Aloia, John F.; Dugas, Lara R.; Tayo, Bamidele O.; Shoham, David A.; Bertino, Anne‐Marie; Yeh, James K.; Cooper, Richard S.; Luke, Amy
<x xml:space="preserve">Abstract</x> Objectives African Americans (AA) have substantially lower levels of circulating 25‐hydroxyvitamin D (25(OH)D) than whites. We compared population‐based samples of 25(OH)D in women of African descent from Nigeria and metropolitan Chicago. Methods One hundred women of Yoruba ethnicity from southwest Nigeria and 94 African American women from metropolitan Chicago were recruited and compared using a standardized survey protocol and the same laboratory assay for 25(OH)D. Results Mean 25(OH)D levels were 64 nmol/l among the Nigerians and 29 nmol/l among the AA. Only 10% of the values were shared in common between the groups, and 76% of the Nigerians were above the currently defined threshold for adequate circulating 25(OH)D compared to 5% of the AA. Modest associations were seen between 25(OH)D and measures of obesity, although adjustment for these traits did not materially affect the group differences. Conclusion These data support the presumption that skin color is an adaptive trait which has evolved in part to regulate 25(OH)D. It remains undetermined, however, whether lower values observed in AA have negative health consequences. Am. J. Hum. Biol. 25:560–562, 2013. © 2013 Wiley Periodicals, Inc.